Extraction and Determination of Sildenafil Citrate by Spectrophotometry: Classical Versus Factorial Design Optimization - A-A Khammas, Zuhair (Tikrit Journal of Pharmaceutical Sciences, 2023)
In this work, the complexation and extraction processes of sildenafil citrate (SC) were evaluated by using classical optimization versus factorial design methodology. The selected factors were based on the reaction of sildenafil with methyl orange (MO) as a chromogenic reagent via the formation of ion-association complex in acidic buffer media, followed by extraction with chloroform and quantitatively measured by visible spectrophotometry at λmax of 427 nm. The optimization step was first carried out by classical one-factor-at-a-time (OFAT) from which the extracted results were exploited in the experimental design optimization by using 24-1 fractional factorial and 32 full factorial designs for the chosen variables such as pH, concentration of reagent, reaction time, extraction time and temperature. Results obtained from fractional factorial design 24-1 showed that only the variables pH, MO concentration and their interaction based on analysis of variance (ANOVA) in term of Pareto chart, were statistically significant at 95% confidence level. Under the optimized conditions, the assay method of SC was validated in term of the analytical figures of merit. SC can be determined in concentration range of 0.5-40 µg mL-1 with correlation coefficient of 0.9991, detection limit (S/N) of 0.15 µg mL-1, RSD (n=10) of 1.43%, accuracy as %Erel of -2.23% and mean percent recovery of 97.77±0.87. The proposed method was applied for the determination of SC in commercial medicaments without fear from excipients interferences with the assay procedure.